A Human Resource Planning and Valuation Model - Gillespie, Jackson Floyd; Leininger, Wayne E.; Kahalas, Harvey (Academy of Management Journal, 1976)
The article presents a study which developed a model that can be applied in the areas of manpower planning and human resource valuation. Background information on the human resource valuation model and the implications of the model for manpower planning and human resource valuation are reviewed. The conclusions reached by the study are discussed.